2019
DOI: 10.1111/cdev.13212
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the Dots Between Past and Future: Constraints in Episodic Future Thinking in Early Childhood

Abstract: Preschoolers have limited capacity to use past experiences to prepare for the future. Two experiments sought to further understand these limitations. Experiment 1 (N = 42) showed that 3‐ to 4‐year olds’ difficulty performing anticipated future actions was constrained by their memory for relevant past actions, especially those including temporal information. Experiment 2 (N = 94) sought to determine whether preschoolers fail to see that past experiences can inform future‐oriented actions. When the connection be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Previous work suggested that children younger than 4 years struggle with multi-step memory-guided planning. Although they can retrieve the relevant knowledge they need to complete a sequence of steps from memory, they have difficulty planning and executing those steps (see, e.g., Blankenship & Kibbe, 2019Prabhakar & Hudson, 2014), which has led to the suggestion that memory-guided planning competence develops between the ages of 3 and 4 (see, e.g., Atance & O'Neill, 2005;Blankenship & Kibbe, 2019;Prabhakar & Ghetti, 2020;Russell et al, 2010). We found that, when the necessary steps of a multi-step plan were presented in a way that encouraged chunking, 3-year-olds were able to complete four-step plans at above-chance levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work suggested that children younger than 4 years struggle with multi-step memory-guided planning. Although they can retrieve the relevant knowledge they need to complete a sequence of steps from memory, they have difficulty planning and executing those steps (see, e.g., Blankenship & Kibbe, 2019Prabhakar & Hudson, 2014), which has led to the suggestion that memory-guided planning competence develops between the ages of 3 and 4 (see, e.g., Atance & O'Neill, 2005;Blankenship & Kibbe, 2019;Prabhakar & Ghetti, 2020;Russell et al, 2010). We found that, when the necessary steps of a multi-step plan were presented in a way that encouraged chunking, 3-year-olds were able to complete four-step plans at above-chance levels.…”
Section: Discussionmentioning
confidence: 99%
“…While the cognitive systems required for memory-guided planning emerge early in life, including explicit memory (Bauer, 1996;Hayne & Herbert, 2004;Rovee-Collier et al, 1980;Richmond & Nelson, 2009), episodic memory (Hayne & Imuta, 2011;Scarf et al, 2011Scarf et al, , 2013Drummey & Newcombe, 2002;Hayne & Imuta, 2011;King & Markant, 2022), and executive control (Rajan et al, 2014;Rajan & Bell, 2015;Espy, 1997;Willoughby et al, 2012), young children often struggle to carry out plans that require drawing on relevant memories to complete multiple steps (Atance & Jackson, 2009;Prabhakar & Ghetti, 2020;Prabhakar & Hudson, 2014;Suddendorf et al, 2011). Blankenship and Kibbe (2019) found that the primary limiting factor on young children's memory-guided planning abilities was the ability to execute a multiple-step plan in the correct sequence.…”
mentioning
confidence: 99%
“…1) to which they refer presents a broad challenge to the dual-systems framework. Children may struggle to retrieve temporal sequences, not because they revert to updating, but rather because of episodic memory retrieval failures (Prabhakar & Ghetti 2019). H&M should enumerate the specific pattern of errors predicted by reverting to the updating system.…”
Section: Second Is a Dual-systems Framework Appropriate?mentioning
confidence: 99%
“…1) to which they refer presents a broad challenge to the dual-systems framework. Children may struggle to retrieve temporal sequences, not because they revert to updating, but rather because of episodic memory retrieval failures (Prabhakar & Ghetti 2019). H&M should enumerate the specific pattern of errors predicted by reverting to the updating system.…”
Section: Temporal Representation and Reasoning In Non-human Animalsmentioning
confidence: 99%